2010
DOI: 10.5424/sjar/2010084-1238
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fruit set and quality in different sweet cherry cultivars

Abstract: The aim of this work is the characterisation of seven cultivars of sweet cherry grown at Murcia (Spain) by determining flower bud density, flower buds drop, number of developing flower buds and total number of flowers per node, fruit set and percentage of double fruits from 2004 to 2007. Also some attributes related to fruit quality, such as fruit weight, colour, soluble solids, total acidity and firmness were evaluated at different ripening stages. 'Brooks' shows high production of flower buds and an appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
4
16
0
2
Order By: Relevance
“…This seems to represent a major advantage for the growers. Similar tendency for fruit weight changes during ripening observed in a previous study on cherry cultivars [14]. Also, earlier work reported a high variability among cherry cultivars regarding this parameter [4,11,12,14,18].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This seems to represent a major advantage for the growers. Similar tendency for fruit weight changes during ripening observed in a previous study on cherry cultivars [14]. Also, earlier work reported a high variability among cherry cultivars regarding this parameter [4,11,12,14,18].…”
Section: Discussionsupporting
confidence: 70%
“…Numerous studies have been done on physical and chemical change in sweet cherries during maturation [12][13][14], while studies on sour cherries are rare. Also, no detailed study concerning physical and chemical properties of sour cherry has been performed up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Our data were similar to the results previously reported for cvs Celeste (Milatović et al 2013), Germersdorfer (Keserović et al 2007) and Sunburst (Glišić et al 2011). Variability in total acidity levels among sweet cherry cultivars was also previously reported (García-Montiel et al 2010).…”
Section: Fruit Chemical Characteristicsmentioning
confidence: 71%
“…Also, blossoming time and duration are important in cherry cultivar selection for planting on spring frost-prone sites. Beside cultivars, most of authors reported that season (year) importantly influenced blossoming date (García-Montiel et al 2010). In addition, climatic conditions can affect fruit set with both low and high temperatures having negative effects.…”
Section: Phenological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation